Pengaruh Metode Sosiodrama terhadap Motivasi Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam MI Al-Hidayah Ciampea Bogor - Muhamad Budi; Ahmad Waki; M. Zainal Arifin (Primer Edukasi Journal, 2022)
The problem examined in this study is to determine whether there is an influence between the use of sociodrama methods on student motivation, especially on SKI lessons. And to find out how much influence between the use of sociodrama methods on student motivation in MI Al-Hidayah Ciampea Bogor. This research is a descriptive correlation study. To conduct this research, a quantitative research approach was used. The sample in this study were all fifth grade students, totaling 23 students. In collecting data used questionnaire and observation techniques. Data analysis used was correlational analysis using the "product moment / Pearson" correlation formula, homogeneity test, significance test, determinant coefficient and simple regression analysis test. After analyzing the data, the results of this study indicate that there is an influence between the Sociodrama Method on Student Learning Motivation in Islamic Cultural History Lessons in MI Al-Hidayah Ciampea Bogor. This is indicated by obtaining the calculated value of 0.335. These results are consistent with the data interpretation table which shows that there is a weak or low correlation. Homogeneity test is obtained Fcount = 1.161 <Ftable = 2.070 then H0 is accepted and concluded that both data groups or both data variables X and Y have the same or homogeneous variants. Significance test was obtained tcount = 1.628. The coefficient of determination is 11% which means that Learning Motivation (variable Y) is influenced by the Sociodrama Method (variable X) by 11%, while the rest is determined by other factors. Keywords: Sociodrama Method, Learning Motivation in Islamic Cultural History Subjects.